2005
DOI: 10.1080/17402520500078204
|View full text |Cite
|
Sign up to set email alerts
|

Insulin as a Primary Autoantigen for Type 1A Diabetes

Abstract: Type 1A diabetes mellitus is caused by specific and progressive autoimmune destruction of the beta cells in the islets of Langerhans whereas the other cell types in the islet (alpha, delta, and PP) are spared. The autoantigens of Type 1A diabetes may be divided into subgroups based on their tissue distributions: Beta-cell-specific antigens like insulin, insulin derivatives, and IGRP (Islet-specific Glucose-6-phosphatase catalytic subunit Related Peptide); neurendocrine antigens such as carboxypeptidase H, insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 56 publications
(69 reference statements)
1
26
0
Order By: Relevance
“…Under more physiological conditions of limited frequencies of β-cell-reactive T cells, low numbers of highly diabetogenic CD4 Consistent with the concept that proinsulin is a major self-Ag and primary target during the early stages of T1D development [78][79][80], low-dosedelivery of whole proinsulin to + DCs in prediabetic NOD mice interfered with the progression towards overt diabetes; 50% of mice that received 4 consecutive injections of 1 µg anti-DECproinsulin mAbs at 2 months of age maintained normoglycemia until the end of the observation period at 6 month of age [63]. In contrast, 90% of NOD mice injected with equivalent amounts of isotype control Ab, or left untreated, had progressed towards overt autoimmune diabetes.…”
Section: Foxp3mentioning
confidence: 88%
“…Under more physiological conditions of limited frequencies of β-cell-reactive T cells, low numbers of highly diabetogenic CD4 Consistent with the concept that proinsulin is a major self-Ag and primary target during the early stages of T1D development [78][79][80], low-dosedelivery of whole proinsulin to + DCs in prediabetic NOD mice interfered with the progression towards overt diabetes; 50% of mice that received 4 consecutive injections of 1 µg anti-DECproinsulin mAbs at 2 months of age maintained normoglycemia until the end of the observation period at 6 month of age [63]. In contrast, 90% of NOD mice injected with equivalent amounts of isotype control Ab, or left untreated, had progressed towards overt autoimmune diabetes.…”
Section: Foxp3mentioning
confidence: 88%
“…Antigenic specificities of intrapancreatic T cells have been mainly defined in the NOD mouse by studies showing that the initial challenge is driven by insulin-specific T cell responses (3,4), later spreading to GAD and other islet-related autoantigens (5,6). In contrast, the T cell targets of human T1D have been identified only from the analysis of peripheral T cells, mostly because of the limited availability of human pancreatic tissue.…”
Section: T Ype 1 Diabetes (T1d) Is An Autoimmune Disease Defined By Tmentioning
confidence: 99%
“…Insulin and glutamic acid decarboxylase 65 (GAD 65 ) are major auto-antigens in type 1 diabetes [23,24] and have been tested in immunomodulation experiments [25]. Data from studies of the spontaneously diabetic NOD mouse have indicated that GAD 65 prevents type 1 diabetes [26,27].…”
Section: Introductionmentioning
confidence: 99%